Integrated antenatal care reduce childbirth anxiety among primigravida women - Nena Riski Hariyati; Abkar Raden; Retno Mawarti; Mula Tarigan (Journal of Health Technology Assessment in Midwifery, 2019)
Pregnant women’s anxiety, if not well-treated, may influence both the physical and psychological conditions of mother and fetus. This study aimed to analyze the correlation between integrated antenatal services and anxiety on facing facing childbirth among primigravida women. This was an observational analytic study used Cross Sectional design. The sample in this study was 55 primigravida women in their third trimester, whom were selected by using a total sampling technique. The study was conducted in a Public Health Centre within Yogyakarta Province. The analysis employed bivariate analysis technique with Chi-Square. The results showed that non-integrated antenatal care had correlation with anxiety about facing labor with p=0.033 and OR=5.417, which explained that non integrated antenatal care significantly increases anxiety among primigravida women. Therefore there is a need tailored services which could improve the quality of Integrated Antenatal Care to reduce pregnant women’s anxiety on facing childbirth.